2015
DOI: 10.1007/s10295-015-1684-8
|View full text |Cite
|
Sign up to set email alerts
|

EasyClone 2.0: expanded toolkit of integrative vectors for stable gene expression in industrial Saccharomyces cerevisiae strains

Abstract: Saccharomyces cerevisiae is one of the key cell factories for production of chemicals and active pharmaceuticals. For large-scale fermentations, particularly in biorefinery applications, it is desirable to use stress-tolerant industrial strains. However, such strains are less amenable for metabolic engineering than the standard laboratory strains. To enable easy delivery and overexpression of genes in a wide range of industrial S. cerevisiae strains, we constructed a set of integrative vectors with long homolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 55 publications
2
54
0
Order By: Relevance
“…). This is comparable with the previous versions of EasyClone, where the targeting efficiency was 80–100% . However, we should note that wrong clones in the EasyClone‐MarkerFree system were not fluorescent and hence they did not contain the designed integration cassettes in their genomes, while for the EasyClone system with selection markers, the integration cassette would always be integrated in the genome, however sometimes it would not be targeted to the designed integration site.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…). This is comparable with the previous versions of EasyClone, where the targeting efficiency was 80–100% . However, we should note that wrong clones in the EasyClone‐MarkerFree system were not fluorescent and hence they did not contain the designed integration cassettes in their genomes, while for the EasyClone system with selection markers, the integration cassette would always be integrated in the genome, however sometimes it would not be targeted to the designed integration site.…”
Section: Resultssupporting
confidence: 80%
“…Genetic manipulation of S. cerevisiae is greatly facilitated by its efficient inherent homologous recombination (HR) machinery for DNA double‐strand break (DSB) repair . As a result, many genome engineering tools have been developed that take advantage of HR for targeted integration of heterologous DNA into the yeast genome . Chromosomal gene integration has several benefits over plasmid‐based approaches, such as increased strain stability, better control of gene expression level and lower population heterogeneity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three years later, in 2014, Jensen and his group designed the EasyClone: a set of vectors that can integrate three cassettes at a time carrying up to two genes each and showed that this is more homogeneous and stable than expressing more than one gene in episomal vectors (Jensen et al ., ). A variation of EasyClone called EasyClone2.0, published in 2015, has the very unique feature of using dominant markers for selection instead of auxotrophy, so it can be applied to prototrophic strains (Stovicek et al ., ). A year later, the EasyCloneMulti collection was created, complementing the latter two.…”
Section: Evolution Of Vector Engineering For Fungimentioning
confidence: 97%
“…CRISPR‐Cas9 has been implemented in a variety of S. cerevisiae backgrounds, including strains used in the brewing and wine industries (Denby et al, ; Gorter de Vries, de Groot, van den Broek, & Daran, ; Vigentini, Gebbia, Belotti, Foschino, & Roth, ) and other industrially relevant yeast species such as fission yeasts (Jacobs, Ciccaglione, Tournier, & Zaratiegui, ), Kluyveromyces marxianus (Lee et al, ), Yarrowia lipolityca (Schwartz & Wheeldon, ; Shi, Huang, Kerkhoven, & Ji, ), Ogatae species (Juergens et al, ), and Pichia species (Weninger et al, ). Of particular relevance is the development of optimized CRISPR‐Cas9 methods to engineer diploid and polyploid industrial yeast strains (Stovicek, Borja, Forster, & Borodina, ; Zhang et al, ). The history and various applications of genome editing have been discussed in‐depth in the following reviews by Fraczek, Naseeb, and Delneri () and Stovicek, Holkenbrink, and Borodina ().…”
Section: Crispr For Rapid Multiplex Engineering Of Cell Factoriesmentioning
confidence: 99%